2022
DOI: 10.5005/jp-journals-10080-1556
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Crossed K-wire Fixation for the Hand Fractures is a Useful Treatment Modality: A Prospective Observational Study

Abstract: A bstract Background Various modalities of treatment have been used for the management of metacarpal and phalangeal fractures which include K-wire fixation, mini plates, lag screws fixation, intramedullary screw fixation and external fixator application. The aim of this study was to analyse complications and patient-related functional outcomes after antegrade or retrograde crossed intramedullary K-wire fixation of metacarpal and proximal phalangeal fractures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Despite these expanded indications, the complication rate observed in our series was similar to what has been published previously on this technique. Previously, studies have reported complication rates for IM screw use in metacarpal fractures to range from 2.5% to 5.3% 23–25 . Our series had a combined postoperative complication rate of 2.9%, comprising of 2 patients.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Despite these expanded indications, the complication rate observed in our series was similar to what has been published previously on this technique. Previously, studies have reported complication rates for IM screw use in metacarpal fractures to range from 2.5% to 5.3% 23–25 . Our series had a combined postoperative complication rate of 2.9%, comprising of 2 patients.…”
Section: Discussionmentioning
confidence: 70%
“…Previously, studies have reported complication rates for IM screw use in metacarpal fractures to range from 2.5% to 5.3%. [23][24][25] Our series had a combined postoperative complication rate of 2.9%, comprising of 2 patients. These included one loss of reduction in an oblique metacarpal neck fracture where the metacarpal head segment fractured postoperatively and subsided proximally off the screw (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 88%